Ferroptosis: A Novel Therapeutic Target for Ischemia-Reperfusion Injury - Chen, Yunqing; Fan, Hongyan; Wang, Shijun; Tang, Guanmin; Zhai, Changlin; Shen, Liang (Frontiers in Cell and Developmental Biology, 2021)
Ischemia-reperfusion (I/R) injury is a major cause of cell death and organ damage in numerous pathologies, including myocardial infarction, stroke, and acute kidney injury. Current treatment methods for I/R injury are limited. Ferroptosis, which is a newly uncovered type of regulated cell death characterized by iron overload and lipid peroxidation accumulation, has been investigated in various diseases. There is increasing evidence of a close association between ferroptosis and I/R injury, with ferroptosis frequently identified as a new therapeutic target for the management of I/R injury. This review summarizes the current status of ferroptosis and discusses its relationship with I/R injury, as well as potential treatment strategies targeting it.